Autologous tumor immunizing devascularization of an invasive colorectal cancer: A case report and literature review - Vašek, Pavel; Krajnik, Josef; Kopsky, David J; Kalina, Vladimir; Frydrych, Marek (Molecular and clinical oncology, 2016)
Colorectal cancer is the third most common cancer. Approximately 20% of patients have at the time of presentation metastasized colorectal cancer, which is incurable in ~80% of cases. The present case report describes a typical case diagnosed with an advanced invasive colorectal adenocarcinoma, with two suspect hypodense lesions in the liver, as revealed by sonography. Judged inoperable for a curative outcome by radical resection, the patient was treated with a novel surgical technique based on stimulating the immune system, termed 'autologous tumor immunizing devascularization' (ATID). The tumor was isolated from its surroundings by ligature of arteries and veins, and subsequently the completely devascularized tumor was left in situ. The distal part of the rectum was closed, and a stoma was made from the proximal part of the colon. Following ATID, the stressing pathophysiological condition of the completely isolated tumor provoked a generalized cellular immune response, which led to the elimination of the devascularized tumor and distant lesions without causing sepsis. The patient did not experience any serious side-effects following the operation, and refused any adjuvant chemo- and/or radiotherapy. To date, the patient has no complaints and remains in good health after the ATID intervention, already more than 14 years. The present case study provides a typical demonstration of the clinical safety of ATID, and also indicates both the immunizing and the curative potential of the method.
Keywords: antigen; ligation; colon and rectum; colorectal neoplasms; immunotherapy; neoplasm; surgery specialty